The Influence of Self-Potential and School Environment on Students' Career Development through the Double Track Program - Risma Nur Azizah; Wilis Werdiningsih (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This study focuses on the career development of students at the senior secondary education level. The purpose of this research is to analyze the influence of self-potential and the school environment on students’ career development through the mediating role of the Double Track Program at SMAN Pilangkenceng. This study employs a quantitative approach using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. Data were collected through questionnaires from 92 students participating in the Double Track Program. The study hypothesizes that self-potential and the school environment have a significant influence on career development, both directly and through the mediating program. The findings indicate that the school environment has a positive and significant effect on students’ career development, both directly and through the Double Track Program, while self-potential shows no significant effect. This research contributes to the field of educational management by highlighting the effectiveness of the Double Track Program as a vocational innovation linking the educational environment with career readiness. The results emphasize the importance of strengthening school support and optimizing program implementation to enhance students’ employability and future career success.